A comprehensive framework for managing human-wildlife conflicts: the case of smallholder livestock depredation by puma (Puma concolor) in the Argentine Dry Chaco - Nanni, Ana Sofia; del Giorgio, Olivia; Cuadrado, Loreley; Dip Yordanoff, Ana L.; Regolin, André Luis [UNESP] (Elsevier, 2025)
Negative impacts of wildlife on livelihoods, such as livestock depredation by carnivores, often lead to human-wildlife conflicts that threaten wildlife populations and human well-being. Despite a growing number, few studies have assessed intervention effectiveness to mitigate such impacts. We present a participatory framework for selecting, implementing, and evaluating interventions targeting human-wildlife conflicts. Applied to a community in the Argentine Dry Chaco to mitigate puma (Puma concolor) livestock depredation, it led to the first test and deployment of a community-selected intervention in the region: studded leather collars placed on small livestock. The proposed framework begins with a stage 1 for characterizing the conflict, consisting of a regional assessment of the broader social-ecological context through interviews, and a local assessment via focus group discussions. It then includes three actionable stages for managing the conflict. Stages 2 and 3 involve selecting and testing potential interventions through a prioritization process based on effectiveness, feasibility, and cost. This led to the selection of studded leather collars, which were evaluated through a randomized controlled trial showing that depredation was ten times higher in the uncollared group. In stage 4, the intervention is fully deployed, which resulted in half the depredation rate to that observed during the trial. Our study demonstrates the effectiveness of studded leather collars in reducing puma attacks on small livestock and highlights the value of integrating local knowledge with evidence-based approaches to address human-wildlife conflicts. This framework can inform effective, context-sensitive strategies and be applied to mitigate conflicts arising from human-wildlife interactions elsewhere.
Um marco conceitual integrado para a gestão de conflitos entre humanos e fauna silvestre: a depredação de rebanhos de pequenos produtores pelo puma (Puma concolor) no Chaco Seco argentino
Keywords: Human-wildlife coexistence; Mmanagement; Pparticipatory research; Ddry woodlands; Impacts; Carnivores